Transformation of Political Campaigns in the Digital Era: Case Studies of Indonesia and Spain - Muhamad Jamal (Yayasan Azhar Amanaa Yogyakarta, 2026)
The coming of the internet era has dramatically influenced political campaigns in Indonesia and Spain. It has improved urban voter engagement and participation in Indonesia by highlighting its most visible work across social media platforms such as Twitter (X-Land) and Facebook in the 2019 and 2020 elections. However, challenges remain in terms of limited knowledge and skills for using digital technology, access problems to the internet, and especially harmful advertising efforts. Given this accuracy problem with surveys and the dissemination of misinformation, the Spanish elections in 2015 and 2019 cemented the role of Twitter (X-Land) data and social bots in extracting information about political communication and voter behavior. In light of these developments in both countries, one can realize that digital tools are taking political campaigns to a different level; appropriate legislation cannot be done without openness, and fairness is guaranteed. The study looks directly at the role of digital campaigns in modern political communication and participation processes, underpinning interactively technological and political relations.